Director tenure diversity and board monitoring effectiveness - LI, Na (Institutional Knowledge at Singapore Management University, 2018)
This study examines the impact of director tenure diversity on board effectiveness. We find that tenure-diverse boards exhibit significantly higher CEO performance-turnover sensitivity and that firms with tenure-diverse audit committees are less likely to experience accounting restatements. Furthermore, we document that tenure-diverse compensation committees also award less excess compensation and are less likely to overcompensate. Even though tenure-diverse boards seem to exhibit superior monitoring performance, there is limited evidence that their firms exhibit superior financial performance. The findings suggest that recent calls for board renewal, to the extent that it would increase tenure diversity rather than just decrease average board tenure, may help enhance board monitoring.